Genetic Transformation in Crops 2020
DOI: 10.5772/intechopen.93012
|View full text |Cite
|
Sign up to set email alerts
|

RNAi Induced Gene Silencing Journey from Simple dsRNA to High-Throughput Intron Hairpin RNA Construct in Crop Improvement

Abstract: RNA interference (RNAi) is the process in which short interfering RNA (siRNA) act to inactivate the expression of target genes. The tremendous work done by many research groups around the globe have contributed in deciphering the RNAi pathway. Understanding the role of siRNA and machinery involved in RNAi pathway led to application of this pathway as technique in therapeutic applications and crop improvement. The specificity of siRNA in interacting the target sequence helped to understand the complex pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Therefore, a FaWRKY1 -intragenic-dsRNAi-inducing unit was designed based on the following considerations: (a) the inverted target sequences correspond to the same 272 bp DNA fragment from the FaWRKY1 described in Higuera-Sobrino et al (2019), which was shown to successfully transiently silence the endogenous FaWRKY1 in strawberry fruit, increasing the resistance of this tissue to C. acutatum ; (b) the length of this FaWRKY1 fragment is within the suitable size to maximize the efficiency of silencing [ 104 ] and its sequence does not drive cross-homology silencing, according to the criteria of Xu et al (2006) (see next section below and Figure 2 ) [ 105 ]; (c) the sense and antisense FaWRKY1 fragments were linked with a 652 bp DNA sequence fragment, corresponding to the native unique FaWRKY1 intron sequence, aimed to act as an internal loop. The inclusion of this functional intron sequence in the sense orientation regarding the promoter is expected to have a consistently-enhancing silencing effect, as previously described [ 106 , 107 , 108 ].…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, a FaWRKY1 -intragenic-dsRNAi-inducing unit was designed based on the following considerations: (a) the inverted target sequences correspond to the same 272 bp DNA fragment from the FaWRKY1 described in Higuera-Sobrino et al (2019), which was shown to successfully transiently silence the endogenous FaWRKY1 in strawberry fruit, increasing the resistance of this tissue to C. acutatum ; (b) the length of this FaWRKY1 fragment is within the suitable size to maximize the efficiency of silencing [ 104 ] and its sequence does not drive cross-homology silencing, according to the criteria of Xu et al (2006) (see next section below and Figure 2 ) [ 105 ]; (c) the sense and antisense FaWRKY1 fragments were linked with a 652 bp DNA sequence fragment, corresponding to the native unique FaWRKY1 intron sequence, aimed to act as an internal loop. The inclusion of this functional intron sequence in the sense orientation regarding the promoter is expected to have a consistently-enhancing silencing effect, as previously described [ 106 , 107 , 108 ].…”
Section: Resultsmentioning
confidence: 80%
“…Thus, a FaNPR3.1 -intragenic-dsRNAi-inducing unit was built on the following criteria: (a) the sense and antisense gene sequences were created using the same 407 bp DNA fragment from the FaNPR3.1 , which successfully transiently silenced the endogenous target gene in strawberry fruit, increasing the resistance of this tissue to C. acutatum [ 114 ]; (b) since the selected 407 bp DNA sequence encompasses nearly identical NPR3 gene alleles but no cross-homology with other members of the strawberry FaNPR gene family that has been detected, only silencing of all putative strawberry Fa NPR3 allele-specific transcripts is expected (see next section below and Figure 3 ); (c) similarly to FaWRKY1, the length of the FaNPR3.1 DNA fragment is appropriate to maximize silencing efficiency [ 104 ] and enhance the silencing effect. The same original FaWRKY1 splicable intron sequence of 652 bp already mention above, was interposed between the FaNPR3.1 -inverted flanking target sequences [ 106 , 107 , 108 ].…”
Section: Resultsmentioning
confidence: 99%